Programa “Alfa Jugando” para la adquisición de lectura y escritura, en estudiantes de primer grado educación primaria -Trujillo, 2019 - Mendoza Vega, Karen Lucía (2021)
The purpose of this research work is to determine if the application of the "Alpha Playing" program improves the level of acquisition of Reading and Writing, in the students of the first grade "A" of primary education of the Educational Institution N ° 80002 "Antonio Torres Araujo” Trujillo, 2019. The type of research is applied with a quasi-experimental design, having an experimental group and a control group. For the present study, a sample of 58 students was selected: 28 from the experimental group and 30 from the control group, whose ages vary between 6 and 7 years. The program “Alpha Playing” was carried out for approximately two months and 16 sessions were applied, which lasted 45 minutes for each session. The results show that the program significantly improved the acquisition of reading and writing in first grade students of the educational institution N° 80002 "Antonio Torres Araujo"